Evaluasi dan Penguatan Sanksi Hukum dalam Penanggulangan Kecurangan (Fraud) pada Sistem Pembayaran Jaminan Kesehatan Nasional (JKN) di Indonesia - Heni Riswanti; Toto Tohir; Alma Lucyanti (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Although JKN aims to provide equitable and quality health services, fraudulent practices, such as phantom billing and diagnosis manipulation, continue to grow, harming BPJS Kesehatan and participants. This study aims to examine the effectiveness of legal sanctions against JKN claim fraud in FKRTL and identify gaps in their implementation. Although regulations are in place, law enforcement remains weak, with administrative sanctions failing to provide sufficient deterrence. The gap in this research lies in the lack of application of criminal sanctions in fraud cases, especially in existing regulations. The novelty of this research is its comparative approach between current administrative sanctions and the potential application of criminal sanctions in the context of healthcare fraud. The research method uses a normative-descriptive approach, analyzing regulations and fraud audit results, and identifying gaps in the implementation of legal sanctions. The results of the study indicate that strengthening criminal sanctions and integrating technology in claim monitoring can increase the effectiveness of fraud prevention. These findings are expected to strengthen regulations and improve the integrity of the JKN system, as well as provide policy recommendations for more effective law enforcement.